A Review: The Effects of Marble Dust on Mechanical Properties and Structural Behavior of Concrete - Heshammuddin, Nurul Atikah; Goh, Wan Inn (Recent Trends in Civil Engineering and Built Environment, 2024)
Marble dusts were produced by the cutting process of metamorphic rocks that frequently used for a sculpture and as a building material. Instead of the good environmental management for marble dust, it is often dumped into an open field. Recent research development has shown that marble dust can be utilized in concrete as a cement replacement material. By replacing marble dust into concrete, the amount of cement can be reduced. Hence, this study is done to review the mechanical properties and structural behavior of concrete incorporating marble dust. Several research through journals, websites and library were prepared to study the effectiveness of marble dust and its characteristics as a cement replacement in concrete mixture. Most of the previous studies shows that the performance of concrete incorporating marble dust is quite good since it can improve the cement particle without any loss of strength. Most of the previous research has investigate the concrete with the various amount of marble as cement replacement (0%, 5%, 10%, 15% and 20%). The samples then were tested to identify the mechanical properties and structural behavior after 7 and 28 days. The compressive strength of the concrete incorporating marble dust increases gradually until 10% of marble dust and start to decrease at 15%. The split tensile strength and flexural strength of the concrete mixture increased with 15% marble dust, but decreased when it reached the limit. The amount of marble dust in concrete admixture to have the higher compressive strength and greater maximum flexural strength compared to conventional concrete is 10%.